INTRODUCTORY p -BANACH ALGEBRAS - A. U. TERRANG; M. T. Y. KADZAI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The researchers identified and defined p -normed algebra and p -Banach algebra on certain quasi-normed spaces such as the space of bounded linear operators ( ( ) L(X Y ) ) Y X L , , ,  defined on quasi-normed spaces ( , ) X X and ) , ( Y Y and the space ) , ( 0 C L  of  -measurable complexvalued functions defined on p -Banach space ( ) p X , , 1 0 p .